MENINGKATKAN HASIL BELAJAR MATA PELAJARAN KIMIA MELALUI PENILAIAN AUTENTIK PADA SISWA KELAS X-1 SMA NEGERI 1 BARAKA KABUPATEN ENREKANG - Arif Candik (Edumaspul: Jurnal Pendidikan, 2017)
The research was aimed at knowing the learning result improvement of Chimetry in class X-1 SMAN 1 Baraka through the autentic assessment. The subject of research was 22 students. The data collection was done by using component of autentic evaluation involving the students asigment, the student jurnal, sain proses skill, examination, and the student behavior during the learning process. The result of research showed that the autentic assessment and the treatment could improve the chemetry learning result of studens class X-1 SMAN 1 Baraka South Sulawesi.